PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICULATE STORYLINE 3 PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR GUGUS IV KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT - Ramadhani, Dina; Mansurdin (Journal of Practice Learning and Educational Development, 2026)
This study aims to develop an interactive learning medium based on Articulate Storyline 3 for the Natural and Social Sciences (IPAS) subject in fifth-grade elementary school, focusing on the sub-topic of economic activities, and to examine its validity, practicality, and effectiveness. This research employed the Research and Development (R&D) method using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. The product was validated by three experts in content, media, and language, then tested on 7 students of a trial school and 18 students of a research school in Gugus IV, Gunung Tuleh District, Pasaman Barat Regency. Data were collected through validation sheets, teacher and student response questionnaires, and pretest-posttest scores, then analyzed descriptively using percentages. The results showed validity scores of 94.64% for content, 96.73% for media, and 96.42% for language, all categorized as very valid. The practicality test yielded 91.66% and 92.85% for teacher and student responses in the trial school, and 95.83% and 90.74% in the research school, all categorized as very practical. The effectiveness test showed classical completeness of 85.71% in the trial school and 100% in the research school, both categorized as very effective. It is concluded that the Articulate Storyline 3-based learning medium is valid, practical, and effective for supporting IPAS instruction in elementary school and can serve as an innovative alternative aligned with the Merdeka Curriculum.